Pengaruh Permen Dark Chocolate terhadap Nyeri Dismenore Primer pada Remaja Putri di SMP Gaya Baru Desa Sumberejo Kecamatan Gedangan Kabupaten Malang - Shanty Natalia; Nita Dwi Astikasari (Universitas STRADA Indonesia, 2019)
The teenagers on menstruation period, sometimes experience the dysmenorrhea pain. Which is medical condition that happened along with menstruation period, and it can disturb the activity, the treatment was needed when the area of stomach or pelvis was so much in pain. The objective of this research is looking for the influence of dark chocolate candy to primary dysmenorrhea pain at adolescent, especially on teenage girl. The design of this research was pre- experimental design that use one group pretest-posttest design with paired T-test analysis. The population of teenage girl was 36, and as many as 26 used as the sampling with the sampling technique using in this research was Random sampling. The technique of data collection was used sheet observation method.